No hay mano invisible (2020)
2001 Nobel Prize laurate, Joseph Stiglitz comments the approaches on experimental economy made by the 2002 laurates, Daniel Kahneman and Vernon Smith. The two academics argue that the economic actors do not behave as rationally as traditional economics believed. This leds to a critique of traditional market economy, specially its idea of a self-regulated market, as stated by Adam Smith and his idea of an “Invisible hand”. Thus, this gives room to an economy not based on ideal models, as that of rational expectations, but on the experimental study of economics as they are, and not as they should be.